Originary Temporality and Existential Commitment: A Defense of Heidegger's A Potiori Claim. (15th January 2016) - Zuckerman, Nate
Abstract: Being and Time 's fundamental ontoogy and existentialism both rest on the A Potiori Claim, which states that originary temporality is, although non‐sequential, a genuine and basic concept of time from which we derive our more ordinary, sequential concept of time. In this paper, I develop a new reading and defense of this claim against the readings of William Blattner, which ties originary temporality too tightly to the particular roles and identities we live out and must therefore find Heidegger's project a failure, and Tony Fisher, who implies that our various roles and identities hang together in time in a merely accidental and non‐rational way. On my reading, originary temporality is the structure of Dasein 's characteristic activity of existential commitment. Through this activity, we each work out, in our own case, what it takes to embody the capacity for sense‐making, at all. Here, the non‐sequentiality of originary temporality reflects the way in which commitments are revised and sustained through time, while the sequence of nows derives from our need to embody our commitment in a single life that negotiates among the practical demands that our various identities make of us.